PENDAMPINGAN PEMBUATAN WEBSITE UNTUK UMKM SATE KEDAI BIRU DAUN - Sudaryanto, Sudaryanto; Hanim, Anifatul; Harsono, Soni Sisbudi; Paramu, Hadi; Endhiarto, Tatok (LP2M Universitas Jember, 2023)
This service activity aims to help MSMEs build digital marketing strategies through creating business websites. The paradigm used is prepositives nominalist qualitative, namely by developing concepts based on environmental conditions. Through direct assistance from the owner of the Biru Daun Sate Depot, planning, implementation, and evaluation of the adoption of information technology to reduce business websites had a positive impact. Observation results show that the business website that was built could generate additional income during the mentoring period.